Adsorption and valence electronic states of nitric oxide on metal surfaces - Shiotari, Akitoshi; Koshida, Hiroyuki; Okuyama, Hiroshi (Surface science reports, 2021)
Among fundamental diatomic molecules, the adsorption of carbon monoxide (CO) and nitric oxide (NO) on metal surfaces has been a subject of intensive research in the surface science community, partly owing to its relevance to heterogeneous catalysis used for environmental control. Compared to the rather well-defined adsorption mechanism of CO, that of NO is less understood because the adsorption results in much more complex reactions. The complexity is ascribed to the open-shell structure of valence electrons, making the molecule readily interact with the metal surface itself as well as with co-adsorbed molecules. Furthermore, the interaction crucially depends on the local structure of the surface. Therefore, to elucidate the interaction at the molecular scale, it is essential to study the valence state as well as the bonding geometry for individual NO molecules placed in a well-defined environment on the surface. Scanning tunneling microscopy (STM) is suitable for this purpose. In this review, we summarize the knowledge about the interaction of NO with metal surfaces, mainly focused on the valence electronic states, followed by recent studies using STM and atomic force microscopy (AFM) at the level of individual molecules.